Dependence of the Morphological Location of the Brittle/Tough Transition on the Modulus of the Dispersed Phase - Zabaleta, Asier; González, Imanol; Eguiazábal, José Ignacio (Macromolecular materials and engineering, 2013)
The dispersed phase of the polypropylene/maleinized poly(ethylene‐octene) (PP/mPEO) blend was modified by means of nanoclay addition, in an attempt to find out the effect of its modulus of elasticity on the location of the brittle/tough (B/T) transition. The nanoclay stayed only in the dispersed rubbery phase upon blending. Upon nanoclay addition, the B/T transition slipped to larger rubber contents; this slip is proposed to be due to the higher modulus of elasticity of the rubbery phase. Looking at the microstructure, the critical interparticle distance (τc) for the B/T transition to occur is less when the dispersed phase is stiffer; i.e., the rubber particles have to be closer to each other for the transition to occur. The dispersed phase of the PP/mPEO blend is modified by means of nanoclay addition via melt mixing. Due to the high affinity of the nanoclay to the maleic anhydride groups of mPEO, the nanoclay stays only in the dispersed rubbery phase. The nanoclay presence causes a displacement of the B/T transition, showing that the stiffer the dispersed rubbery phase is, the larger the rubber content necessary for the B/T transition to occur.